RNA-Seq Analyses Reveal That Endothelial Activation and Fibrosis Are Induced Early and Progressively by Besnoitia besnoiti Host Cell Invasion and Proliferation - Jiménez-Meléndez, Alejandro; Ramakrishnan, Chandra; Hehl, Adrian B.; Russo, Giancarlo; Álvarez-García, Gema (Frontiers in Cellular and Infection Microbiology, 2020)
The pathogenesis of bovine besnoitiosis and the molecular bases that govern disease progression remain to be elucidated. Thus, we have employed an in vitro model of infection based on primary bovine aortic endothelial cells (BAEC), target cells during the acute infection. Host-parasite interactions were investigated by RNA-Seq at two post-infection (pi) time points: 12 hpi, when tachyzoites have already invaded host cells, and 32 hpi, when tachyzoites have replicated for at least two generations. Additionally, the gene expression profile of B. besnoiti tachyzoites was studied at both pi time points. Up to 446 differentially expressed B. taurus genes (DEGs) were found in BAEC between both pi time points: 249 DEGs were up-regulated and 197 DEGs were down-regulated at 32 hpi. Upregulation of different genes encoding cytokines, chemokines, leukocyte adhesion molecules predominantly at 12 hpi implies an activation of endothelial cells, whilst upregulation of genes involved in angiogenesis and extracellular matrix organization was detected at at both time points. NF-κB and TNF-α signalling pathways appeared to be mainly modulated upon infection, coordinating the expression of several effector proteins with proinflammatory and pro-fibrotic phenotypes. These mediators are thought to be responsible for macrophage recruitment setting the basis for chronic inflammation and fibrosis characteristic of chronic besnoitiosis. Angiogenesis regulation also predominated, and this multistep process was evidenced by the upregulation of markers involved in both early (eg. growth factors and matrix metalloproteinases) and late steps (eg. integrins and vasohibin). Besnoitia besnoiti orthologue genes present in other Toxoplasmatinae members and involved in the lytic cycle have shown to be differentially expressed among the two time points studied, with a higher expression at 32 hpi (eg. ROP40, ROP5B, MIC1, MIC10). This study gives molecular clues on B. besnoiti- BAECs interaction and shows the progression of type II endothelial cell activation upon parasite invasion and proliferation.